Double mutations in the H9N2 avian influenza virus PB2 gene act cooperatively to increase viral host adaptation and replication for human infections. (1st June 2021) - Elgendy, Emad Mohamed; Arai, Yasuha; Kawashita, Norihito; Isobe, Ayana; Daidoji, Tomo; Ibrahim, Madiha Salah; Ono, Takao; Takagi, Tatsuya; Nakaya, Takaaki; Matsumoto, Kazuhiko; Watanabe, Yohei
Abstract : Avian H9N2 influenza viruses in East Asia are genetically diversified and multiple genotypes (A-W) have been established in poultry. Genotype S strains are currently the most prevalent strains, have caused many human infections and pose a public health threat. In this study, human adaptation mutations in the PB2 polymerase in genotype S strains were identified by database screening. Several PB2 double mutations were identified that acted cooperatively to produce higher genotype S virus polymerase activity and replication in human cells than in avian cells and to increase viral growth and virulence in mice. These mutations were chronologically and phylogenetically clustered in a new group within genotype S viruses. Most of the relevant human virus isolates carry the PB2-A588V mutation together with another PB2 mutation (i.e. K526R, E627V or E627K), indicating a host adaptation advantage for these double mutations. The prevalence of PB2 double mutations in human H9N2 virus isolates has also been found in genetically related human H7N9 and H10N8 viruses. These results suggested that PB2 double mutations in viruses in the field acted cooperatively to increase human adaptation of the currently prevalent H9N2 genotype S strains. This may have contributed to the recent surge of H9N2 infections and may be applicable to the human adaptation of several other avian influenza viruses. Our study provides a better understanding of the human adaptation pathways of genetically related H9N2, H7N9 and H10N8 viruses in nature.